Empowering Leaders: Transformational Leadership Training in Nepal (Journal of Psychiatrists' Association of Nepal, 2026)
In November 2023, the Psychiatrists’ Association of Nepal conducted a leadership course for psychiatrists for the first time in Nepal. Leadership program holds great value among psychiatrists, especially in their early careers, from around the world. Many of the participants who attended it described it as a life-changing experience. We aim to provide a brief narrative and highlight the importance of conducting such courses.